The asymmetric synthesis of D-galactose via an iterative syn-glycolate aldol strategy - Davies, S; Nicholson, R; Smith, A (2002)
The asymmetric synthesis of D-galactose has been completed in eight steps and in >14% yield from simple starting materials via an iterative syn-glycolate aldol strategy.